Outcome of Lumbar Drain in Delayed Communicating Hydrocephalus Secondary to Traumatic and Aneurysmal Subarachnoid Hemorrhage - Roka, Yam Bahadur (Nepal Journal of Neuroscience, 2020)
Introduction: Delayed hydrocephalus is one of the common complications in traumatic subarachnoid hemorrhage and post aneurysmal subarachnoid hemorrhage. This study aims to study the role of lumbar drain in its management. Methods: This is a retrospective study of cases of delayed hydrocephalus which were managed with lumbar drain between March 2009 to February 2019. Computed tomogram or Magnetic Resonance Imaging was used in the diagnosis of delayed hydrocephalus and lumbar drain was inserted. A repeat Computed tomogram scan was performed, and the absence of delayed hydrocephalus was the indication for removal. Results: A total of 40 cases of delayed hydrocephalus were managed with lumbar drain during the study period. Traumatic subarachnoid hemorrhage was the cause of delayed hydrocephalus in 16 cases and the remaining 24 cases were due to post aneurysmal subarachnoid hemorrhage. The most common Fischer grade was III in aneurysm and II in trauma. Delayed hydrocephalus occurred within two to four weeks in aneurysm cases and after four weeks in traumatic cases. All aneurysm was managed with clipping whereas craniotomy or decompressive craniectomy was done in traumatic cases. 92.5% of cases improved after lumbar drainage of the hydrocephalus. Conclusion: This study reports the use of lumbar drain to treat delayed post subarachnoid hemorrhage hydrocephalus in a clinically-cost-effective way with minimal complications. Randomized studies to compare methods to treat delayed hydrocephalus will overcome the limitations of this study. Till then lumbar drain remains a safe alternative in communicating delayed hydrocephalus secondary to subarachnoid hemorrhage.